Analisis Pengembangan Desa Wisata di Desa Sumber Urip, Rejang Lebong, Bengkulu - Dayu Silviana; Marwan Arwani; Ika Pasca Himawati (Jurnal Sosiologi Andalas, 2021)
This study aims to explain the stretching of the tourism village development in terms of the form of community participation. Research uses qualitative descriptive approach, the analysis is carried out using the exchange theory. The research results show the form of participation by the community can be seen from the construction of tourist facilities. Pokdarwis involvement as a tourism manager is carried out by taking four stages of participation: namely, participation in planning through the activity of conveying ideas in the form of criticism and suggestions at the planning meeting for tourism village development activities. Furthermore, the implementation stage is manifested in the form of personnel participating in the form of mutual assistance activities to improve the condition of tourist facilities, environmental maintenance by cleaning up trash on the hiking trail and becoming parking guards. On the other hand, the form of skill participation carried out by the community is manifested through activities of making tourist souvenirs and promotion on social media. Meanwhile, the utilization stage is carried out through efforts to open business opportunities and opportunities for youth who do not have a job. Finally, the evaluation stage is carried out by taking a comparative study activity to other Tourism Villages as a comparison to see the success of the Bukit Kaba Tourism Village.